Penguatan Peran Kelompok Pemberdayaan Kesejahteraan Keluarga Dalam Menjaga Kesehatan Lingkungan Di Desa Kemudo - Sarwendah Dwi Juniati; Novi Danisa Halimah Azzahra; Ryan Miftahul Hidayat; Khairana Nur Shabrina; Alifiah Azzahra; Akbar Aristyo Pambudi (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2024)
The KKN 35 UNS group carried out activities aimed at addressing environmental health issues faced by the community of Kemudo Village, including household waste management and dengue fever. Efforts made by the students involved training in composting and socialization on dengue fever prevention using lavitraps. Training and socialization targeted PKK with the aim of strengthening the role of PKK in addressing environmental health issues in their village. Training involved practicing the compost making process and distributing compost making equipment. Meanwhile, socialization included delivering materials related to dengue fever, explaining lavitraps, and distributing lavitraps made by the students. The training activities received a positive response, as demonstrated by the active participation of PKK during compost making practice. The socialization activities also received positive responses as lavitraps were deemed innovative and quite effective in reducing mosquito breeding in homes.